2017
DOI: 10.3892/br.2017.991
|View full text |Cite
|
Sign up to set email alerts
|

Association of smoking with prevalence of common diseases and metabolic abnormalities in community-dwelling Japanese individuals

Abstract: Abstract.Smoking is a significant risk factor for cardiovascular diseases (CVDs). Given that certain common pathologies, including hypertension, dyslipidemia and type 2 diabetes mellitus, are major risk factors for CVDs, the association of smoking with CVDs may be attributable, at least in part, to its effects on common diseases. The aim of the present study was to determine the association of smoking with the prevalence of common diseases and metabolic abnormalities in community-dwelling Japanese individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Similar behavior was seen in the ICMR-INDIAB cross-sectional study 41 of 16,607 adult individuals, which showed a positive correlation between high TAG levels and smoking. Ueyama et al 42 reported there was a positive association between smoking and high TAG levels in a study of 5959 Japanese individuals. This phenomenon could be explained by the fact that stimulation of the sympathetic nervous system produces the release of insulin antagonists.…”
Section: Discussionmentioning
confidence: 96%
“…Similar behavior was seen in the ICMR-INDIAB cross-sectional study 41 of 16,607 adult individuals, which showed a positive correlation between high TAG levels and smoking. Ueyama et al 42 reported there was a positive association between smoking and high TAG levels in a study of 5959 Japanese individuals. This phenomenon could be explained by the fact that stimulation of the sympathetic nervous system produces the release of insulin antagonists.…”
Section: Discussionmentioning
confidence: 96%
“…Similar behavior was seen in the ICMR-INDIAB cross-sectional study 43 of 16,607 adult individuals, which showed a positive correlation between high TAG levels and smoking. Ueyama et al 44 reported there was a positive association between smoking and high TAG levels in a study of 5959 Japanese individuals. This phenomenon could be explained by the fact that stimulation of the sympathetic nervous system produces the release of insulin antagonists.…”
Section: Discussionmentioning
confidence: 96%
“…Data showed that smoking was a protective factor for the accumulating of key stroke risk factors in our study. Although smoking was a risk factor for diabetes and hyperlipidemia ( 27 , 28 ), Mehboudi's study indicated an inverse association between smoking and hypertension in an elderly population in Iran ( 29 ), and Wang's study indicated that smokers were less likely to be overweight or obese ( 15 ). These findings might explain why smoking was a protective factor for the accumulating of key stroke risk factors in our study.…”
Section: Discussionmentioning
confidence: 99%